2021
DOI: 10.1061/(asce)up.1943-5444.0000734
|View full text |Cite
|
Sign up to set email alerts
|

Purchase Motivation, Landscape Preference, and Housing Prices: Quantile Hedonic Analysis in Guangzhou, China

Abstract: Urban landscapes are important factors that affect housing prices, and significant differences between landscape preferences of various homebuyers may be observed because of the different reasons for purchasing a house (consumption or investment). However, the hedonic price model widely applied in most existing studies only captures the average effects of landscapes as a whole sample, and may ignore the heterogeneity of landscape preferences. To fill this gap, this study constructed hedonic price models and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Therefore, considering that buyers in different income groups have different willingness to pay for ecological landscapes, the impact of ecological landscape on high, medium and low-value properties may also be heterogeneous. Wen et al (2021) explored the internal relationship between landscape pref-erences and home values of different types of homebuyers based on Hedonic Pricing Method and Quantile Regression Model. The study showed that buyers who buy high-priced houses are more willing to pay for attractive landscapes than those who buy low-priced houses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering that buyers in different income groups have different willingness to pay for ecological landscapes, the impact of ecological landscape on high, medium and low-value properties may also be heterogeneous. Wen et al (2021) explored the internal relationship between landscape pref-erences and home values of different types of homebuyers based on Hedonic Pricing Method and Quantile Regression Model. The study showed that buyers who buy high-priced houses are more willing to pay for attractive landscapes than those who buy low-priced houses.…”
Section: Introductionmentioning
confidence: 99%